Does systemic clarithromycin therapy have an inhibitory effect on tympanosclerosis? An experimental animal study. Issue 2 (February 2015) - Genc, G; Koyuncu, M; Kutlar, G; Guvenc, T; Gacar, A; Aksoy, A; Arslan, S; Kurnaz, S C
Abstract Objective: To demonstrate the inhibitory effects of clarithromycin on in vitro tympanosclerosis. Method: Twenty-eight rats were divided into three groups: a clarithromycin group, a non-clarithromycin group and a negative control group. Those in the first two groups were injected with Streptococcus pneumoniae following a myringotomy, and tympanosclerosis was experimentally induced. Oral clarithromycin therapy was administered in the clarithromycin group. The other groups received no medical treatment. Results: All eardrums in the clarithromycin and non-clarithromycin groups developed myringosclerosis, but there was only one eardrum, in the clarithromycin group, with very severe myringosclerosis. In the clarithromycin group, 11 ears showed no inflammation and there were no ears with severe inflammation. In the non-clarithromycin group, there were 11 ears with severe inflammation. The mean eardrum thickness in the clarithromycin group was 20.93 µm and in the non-clarithromycin group it was 42.71 µm. Conclusion: Acute otitis media and myringotomies induced tympanosclerosis, but clarithromycin reduced the severity of tympanosclerosis.